Development and study of characteristics of stripped detectors on the basis of CVD-diamond - Kutny, V.E.; Vierovkin, A.A.; Rybka, A.V.; Dudnik, S.F.; Opalev, O.A.; Strelnitsky, V.E.; Zakharchenko, A.A.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2016)
The prototypes of the coordinate-sensitive semiconductor detectors based on polycrystalline diamond films (CVD-diamond) have been manufactured in the NSC KIPT. In this communication, a version of the detector with the strip-type contacts and its characteristics are described. The techniques of the detector calibration both as a whole and for separate groups of the strips against the absorbed dose rate of the electron and bremsstrahlung radiation are developed. By means of the computer simulations, an independent analysis of conditions of the radiation field registration with the detector has been conducted. The experiments carried out at the LU-10 accelerator at NSC KIPT have shown that the sensitivities of the separate elements (strips) of the detector are similar. The results of the measurements of the volume sensitivity of the detector are in agreement with the data received earlier for a singlecontact detector. The possibility of the detector application in the study of transverse dynamics of an electron beam is shown.